Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/diagnostics11071163
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Antibody Detecting Rapid Diagnostic Tests Show High Cross-Reactivity When Challenged with Pre-Pandemic Malaria, Schistosomiasis and Dengue Samples

Abstract: COVID-19 Antibody Detecting Rapid Diagnostic Tests (COVID-19 Ab RDTs) are the preferred tool for SARS-CoV-2 seroprevalence studies, particularly in low- and middle-income countries. The present study challenged COVID-19 Ab RDTs with pre-pandemic samples of patients exposed to tropical pathogens. A retrospective study was performed on archived serum (n = 94) and EDTA whole blood (n = 126) samples obtained during 2010–2018 from 196 travelers with malaria (n = 170), schistosomiasis (n = 25) and dengue (n = 25). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 65 publications
(113 reference statements)
3
28
0
Order By: Relevance
“…A weak but statistically significant positive correlation was detected between spike and RBD with AMA-1 IgG ( Figure 2 , panel D). This finding corroborates recent observations that higher SARS-CoV-2 seroreactivity by ELISA or rapid tests is detected in persons from malaria-endemic areas, expanding previous observations to include Southeast Asia ( 7 , 8 ; S. Lapidus et al, unpub. data).…”
Section: The Studysupporting
confidence: 91%
See 1 more Smart Citation
“…A weak but statistically significant positive correlation was detected between spike and RBD with AMA-1 IgG ( Figure 2 , panel D). This finding corroborates recent observations that higher SARS-CoV-2 seroreactivity by ELISA or rapid tests is detected in persons from malaria-endemic areas, expanding previous observations to include Southeast Asia ( 7 , 8 ; S. Lapidus et al, unpub. data).…”
Section: The Studysupporting
confidence: 91%
“…These antibody-based studies are necessary to determine at-risk populations and direct disease containment measures; however, before informing public health decisions, serologic assays require careful, country-specific calibration because several regions report fluctuating results or high background reactivity in different populations ( 3 5 ). This variability might be attributable to myriad serologic assays, the hypothesized cross-reactivity from common cold–type respiratory coronaviruses ( 6 ), previous Plasmodium infections ( 7 , 8 ; S. Lapidus et al, unpub. data, https://www.medrxiv.org/content/10.1101/2021.05.10.21256855v1 ), or previously uncharacterized betacoronaviruses in wildlife populations in the rural GMS ( 9 11 ).…”
mentioning
confidence: 99%
“…Since SLE is a condition characterized by a broad repertoire of circulating autoantibodies, it is not unlikely that this group of patients in general may be more prone to produce antibodies targeting various antigens, including coronaviruses, even in the absence of COVID-19. In line with this, it was recently demonstrated that certain infections (e.g., malaria, schistosomiasis, and dengue) may yield unreliable results in rapid diagnostic COVID-19 antibody tests (37). Some betacoronaviruses have been described as capable of inducing ELISA and Western blot cross-reactive anti-SARS-CoV-2 serum responses, but in general not cross-neutralizing antibodies (38)(39)(40).…”
Section: Discussionmentioning
confidence: 95%
“…Before this study, we previously assumed that COVID-19 and dengue diagnoses could be affected by a misclassification bias which could stem from the poor sensitivity of both SARS-CoV-2 molecular and DENV NS1 antigen tests rather than from their false positives [ 9 ]. This putative bias was believed to be minimal given that, firstly, on Reunion Island, like anywhere else during the rise of the COVID-19 pandemic [ 21 ], there was little cocirculation of other respiratory viruses that could have competed with SARS-CoV-2 and caused false negatives, [ 22 ], and secondly, for COVID-19, negative samples were retested by RT-PCR upon onset of new symptoms, meaning that rapid antibody or antigenic tests were ruled out, while for dengue, the workup was completed by a RT-PCR or a serology test to downsize false negative and false positive proportions [ [23] , [24] , [25] ]. This caution decision rule likely pledges the diagnostic accuracy of our gold standards.…”
Section: Discussionmentioning
confidence: 99%